MANAGING EDUCATIONAL PERSONNEL IN MADRASAH ALIYAH: A MANAGERIAL APPROACH TO IMPROVING EDUCATIONAL SERVICE QUALITY - Mawardi, Mawardi; Nasimin, Nasimin; Novita, Mona; Amin, Muhammad (Universitas Islam Negeri (UIN) Sumatera Utara, 2023)
Educational service quality has become an essential concern in the governance of Islamic educational institutions, particularly Madrasah Aliyah, where administrative and academic support services play a strategic role in sustaining effective teaching and learning processes. However, existing studies in Islamic education management have predominantly emphasized the roles of principals and teachers, while the managerial contribution of educational personnel has received limited scholarly attention. This study aims to analyze the management of educational personnel roles in Madrasah Aliyah and to develop a managerial model oriented toward improving educational service quality. Using a qualitative approach, data were collected through in-depth interviews, observations, and document analysis conducted in one state and one private Madrasah Aliyah in Kabupaten Sarolangun, Indonesia. The findings reveal several persistent managerial problems, including role ambiguity, overlapping responsibilities, weak coordination mechanisms, the absence of standardized service procedures, and non-systematic performance evaluation practices. These conditions result in reactive and inconsistent educational service delivery. Based on the synthesis of empirical findings, this study proposes a managerial model that integrates role structuring, job description formulation, institutional coordination mechanisms, SOP-based service standardization, service-indicator-based performance evaluation, and leadership supervision. The proposed model positions educational personnel as strategic actors within the educational service system and provides an empirically grounded framework for strengthening service consistency, accountability, and continuous improvement. This study contributes to the field of Islamic Education Management by offering a contextual managerial model that addresses an underexplored dimension of educational service quality in madrasahs.